2014
DOI: 10.1007/s11604-014-0320-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of scanning parameters for MR elastography at 3.0 T clinical unit: volunteer study

Abstract: With the optimized parameters, repeatability of ±10 % in liver stiffness measurement was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…P values are less than 0.05 for the first three parameters, but larger than 0.05 for the fourth parameter, F1 vs F2. Therefore, the first three parameters, namely F3 vs F4, A0-1 vs A2-3, and F0-1 vs F2, are considered significant FS forward selection, AICc corrected Akaike's information criterion, BIC Bayesian information criterion, F/A degrees of liver fibrosis and necroinflammation of the liver according to the Metavir system [25,26] obtained exclusively from patients with chronic hepatitis C infection [19] are apparently lower than those for patients with chronic hepatitis B infection [22]. Other possible reasons are technical differences, including those in the pulse sequence used (gradient-echo vs echo-planar), imaging parameters, inversion algorithm, ROI placement method [24] etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…P values are less than 0.05 for the first three parameters, but larger than 0.05 for the fourth parameter, F1 vs F2. Therefore, the first three parameters, namely F3 vs F4, A0-1 vs A2-3, and F0-1 vs F2, are considered significant FS forward selection, AICc corrected Akaike's information criterion, BIC Bayesian information criterion, F/A degrees of liver fibrosis and necroinflammation of the liver according to the Metavir system [25,26] obtained exclusively from patients with chronic hepatitis C infection [19] are apparently lower than those for patients with chronic hepatitis B infection [22]. Other possible reasons are technical differences, including those in the pulse sequence used (gradient-echo vs echo-planar), imaging parameters, inversion algorithm, ROI placement method [24] etc.…”
Section: Discussionmentioning
confidence: 99%
“…A 60-Hz waveform was applied to the driver. A 2D spin-echo echo-planar MRE sequence (TR/TE=1000/59, 66×64 matrix, 10 mm slice thickness, 80-Hz magnetization encoding gradient) acquired magnitude and unwrapped phase difference wave images using a 42-cm field-of-view [25]. Four slices were obtained including the level of the hepatic hilum under 16-s breath-holding.…”
Section: Mr Elastographymentioning
confidence: 99%
See 1 more Smart Citation
“…With reference to the cross-hatching area, we found that an MEG of 60 Hz, an external driver frequency of 40 Hz, and an amplitude of 50% were optimal in this system. The precise reason why a MEG frequency that is not equal to the external driver frequency works better is unclear; however, this technique has been widely used in the MRE literature as a means to reduce TE 22 or to create broadband sensitivity for multifrequency MRE. [23][24][25][26] Although the spatial resolution in our system was very low because of the low external driver frequency and limited matrix size, the shear stiffness of healthy regions of the brain such as the cerebellum was consistent among patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study suggested that slightly different stiffness values may be obtained using different parameter settings. 70 Therefore, it would be necessary to show the reproducibility of the MRE results using various field strengths and scanners from different manufacturers to validate the accuracy and reproducibility of MRE.…”
Section: Discussionmentioning
confidence: 99%